Empowering Flight Exercise: Teaching Students the Design, Underlying Processes, and Organizational Outcomes of Empowering Work Systems. (March 2023) - Gardner, Timothy M.; Romney, Alexander C.
Employee empowerment yields positive outcomes for employees, managers, and organizations. Yet, too many employees feel disempowered at work, and managers, while wanting to empower employees, often do not know how. Contributing to this state of affairs is the lack of published, high-fidelity exercises explicitly designed to instruct students on how empowerment "feels, " how empowerment "works, " and how to practically empower others. In this article, we outline a 90-minute face-to-face classroom exercise that integrates the structural and psychological empowerment perspectives enabling students to "feel" empowerment or disempowerment and see the productivity and quality benefits of an empowered workforce, and teaches students how to empower others at work. While participating in the exercise, students simulate working in an airplane manufacturing organization, working either in an empowered work environment or a traditional hierarchical work environment. The exercise provides instructors with an important classroom tool to instruct students about the importance of empowerment, trust, and performance in organizational life.